Review of Natural Resources With Vasodilation: Traditional Medicinal Plants, Natural Products, and Their Mechanism and Clinical Efficacy - Tang, Fei; Yan, Hong-Ling; Wang, Li-Xia; Xu, Jin-Feng; Peng, Cheng; Ao, Hui; Tan, Yu-Zhu (Frontiers in Pharmacology, 2021)
For decades, chronic diseases including cardiovascular and cerebrovascular diseases (CCVDs) have plagued the world. Meanwhile, we have noticed a close association between CCVDs and vascular lesions, such as hypertension. More focus has been placed on TMPs and natural products with vasodilation and hypotension. TMPs with vasodilatory and hypotensive activities are mainly from Compositae, Lamiaceae and Orchidaceae (such as V. amygdalina Del., T. procuinbens L., M. glomerata Spreng., K. galanga L., etc.) whereas natural products eliciting vasorelaxant potentials were primarily from flavonoids, phenolic acids and alkaloids (such as apigenin, puerarin, curcumin, sinomenine, etc.). Furthermore, the data analysis showed that the vasodilatory function of TMPs was mainly concerned with the activation of eNOs, while the natural products were primarily correlated with the blockage of calcium channel. Thus, TMPs will be used as alternative drugs and nutritional supplements, while natural products will be considered as potential therapies for CCVDs in the future. This study comprehensive and valuable references for the prevention and treatment of hypertension and CCVDs and sheds light on the further studies in this regard. However, since most studies are in vitro and preclinical, there is a need for more in-depth researches and clinical trials to understand the potential of these substances.